(untitled) (Research, Society and Development, 2018)
This article aimed to verify the existence of the Quality Management System in a fridge. For that, a qualitative research, of exploratory character and classified as to the procedures, was carried out as a case study. For the data collection, the structured interview technique was used. For the interpretation of the data, the technique of discourse analysis was used. The main results pointed out that the company does not fit into the quality systems approached throughout the article, such as the Total Quality Management system, 5S, or Statistical Quality Control. It aims at quality based on mandatory programs, such as health surveillance and also state inspection of the product. On the other hand, the company uses Quality Management, as it understands that it can bring more efficiency and competitive security. It should be emphasized that the fridge uses Quality Management in its processes by monitoring the employees themselves in the temperature control of the cold rooms and PH of the meat, in order to avoid production errors and to guarantee the quality of the products.